2004
DOI: 10.1029/2003ja010366
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of a global MHD code and an inner magnetospheric model: Initial results

Abstract: [1] This paper describes the coupling of BATS-R-US (Block Adaptive Tree Solar-wind Roe-type Upwind Scheme), a magnetohydrodynamics (MHD) code representing the Earth's global magnetosphere and its coupling to the ionosphere and solar wind, and the Rice Convection Model (RCM), which represents the inner magnetosphere and its coupling to the ionosphere. The MHD code provides a time-evolving magnetic field model for the RCM as well as continuously updated boundary conditions for the electric potential and plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
284
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(293 citation statements)
references
References 63 publications
9
284
0
Order By: Relevance
“…Then, it is very reasonable to suggest that the relaxation of these pressure gradients after the northward turning of B z IMF and the reduction in the sunward convection, occurs on the same time scale, inferring the persistence of the shielding (dusk-to-dawn) electric field for about an hour. The validity of this suggestion has been proved in the computer simulation of De Zeeuw et al (2004). Using the RCM MHD code, the authors showed that about 10 min after the northward turning of the IMF reaches the magnetopause the inner magnetosphere exhibits an overshielding electric field which lasts just over an hour.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Then, it is very reasonable to suggest that the relaxation of these pressure gradients after the northward turning of B z IMF and the reduction in the sunward convection, occurs on the same time scale, inferring the persistence of the shielding (dusk-to-dawn) electric field for about an hour. The validity of this suggestion has been proved in the computer simulation of De Zeeuw et al (2004). Using the RCM MHD code, the authors showed that about 10 min after the northward turning of the IMF reaches the magnetopause the inner magnetosphere exhibits an overshielding electric field which lasts just over an hour.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the Region 2-type FACs, which arise in the nighttime near-Earth tail during the growth phase (Fig. 2), are related to the pressure gradients developing here and thus have much a larger relaxation time of ∼1 h (Rezhenov et al, 1980;De Zeeuw et al, 2004). During this period they solely control the convection in the inner magnetosphere.…”
Section: Finding Equilibrium Statementioning
confidence: 99%
See 2 more Smart Citations
“…Fejer et al [1990] proposed that the magnetic field reconfiguration of the magnetosphere due to a northward turning and the associated shrinkage of the polar cap may effectively prolong the overshielding time period. This effect has been confirmed by the Rice Convection Model (RCM) with a time-dependent magnetic field model [Sazykin, 2000;De Zeeuw et al, 2004;Maruyama et al, 2007;Zhang et al, 2009] and has been discussed with observations [Wei et al, 2008b[Wei et al, , 2009. On the other hand, the IMF northward turning is preferable to trigger substorms [Lyons et al, 1997], but the effect of substorm on overshielding, reduction [e.g., Huang et al, 2004;Huang, 2009] or enhancement [Wei et al, 2009;Zhang et al, 2009] is still a controversial issue.…”
Section: Introductionmentioning
confidence: 85%